Penerapan Pendekatan SAVI Untuk Meningkatkan Aktivitas Dan Hasil Belajar IPA Pada Siswa Kelas IV SD Negeri Joho 02 Sukoharjo Tahun 2015/2016 - Pangesti, Fadiyah Daning (2016)
Classroom action research aims to improve the learning process which is less optimal. Problems that occur in the classroom, especially in science learning about the low activity of learning and student learning outcomes, this study aims to (1) increase the activity of class IV study science subjects, (2) improve learning outcomes of fourth grade students. This type of research is used PTK. The study was conducted during two cycles, each cycle two meetings. Classroom action research conducted at SDN 02 Joho Sukoharjo 2016 the number of students 30. Based on the results obtained during the study of prasiklus, the first cycle, the second cycle continues meningkat.The result obtained based on the indicators of learning activities: (1) activity in asking for 23.33 %, 35% and 51.66% (2) activity in answering questions 16.66%, 29.99% and 45% (3) activity in opine 10%, 25% and 39.99% (4) activity in working on the problems of 46.66%, 59.99% and 85% (5) activity in discussions 33.33%, 54.99% and 79.99% The results of learning acquired 66.83%, 74.76% and 88, 86% It can be concluded implementation SAVI approach to learning science learning activities and improve learning outcomes of fourth grade students of SDN 02 Joho Sukoharjo 2016.